Curriculum strategy framework: investigating patterns in teachers’ use of a reform‐based elementary mathematics curriculum - Sherin, Miriam Gamoran; Drake, Corey (Journal of Curriculum Studies, 2009)
The goal of this paper is to introduce the curriculum strategy framework as a way to characterize teachers’ interactions with curriculum materials. The framework focuses on three key interpretive activities: reading, evaluating, and adapting curriculum materials. Describing an individual teacher’s curriculum strategy involves identifying the manner in which a teacher engages with each of these activities before, during, and after instruction. This paper presents the results of a study in which the framework was used to identify patterns in the curriculum strategies of 10 elementary‐school teachers who were using a reform‐based mathematics curriculum for the first time. It concludes with directions for further research using the curriculum strategy framework, and implications of this work for curriculum designers.